Mapping the Incidence of Infestation by Neoechinorhynchus buttnerae (Acanthocephala) Parasitizing Colossoma macropomum Raised in Fish Farms and the Relationship with Zooplankton Ostracods and Copepods - Vinicius Perez Pedroti; Jerônimo Vieira Dantas Filho; Átila Bezerra de Mira; Maria Mirtes de Lima Pinheiro; Bruna Lucieny Temponi Santos; Raniere Garcez Costa Sousa; Jucilene Braitenbach Cavali; Ed Johnny da Rosa Prado; Sandro de Vargas Schons (Veterinary Sciences)
This study investigated the abundance of zooplankton copepods and ostracods taxonomic groups in fish farms in Rondônia’s Vale do Jamari and Centro-Leste microregions during the rainy and dry seasons. It also analyzed the correlation between zooplanktons abundance and the presence of acanthocephalan parasites. Conducted in 41 fish farms between November 2021 and September 2023, the study included water, zooplankton, and fish samples from 196 Colossoma macropomum. The results showed that 95% of the farms had fish infected with Neoechinorhynchus buttnerae, with varying parasitism levels. Georeferencing revealed higher parasite densities in the municipalities of Ariquemes, Monte Negro, Machadinho do Oeste, and Buritis (Vale do Jamari), as well as Urupá, Ji-Paraná, Ouro Preto do Oeste, and Teixeirópolis (Centro-Leste), with clusters of heat islands in the latter group. Water quality parameters were suitable for raising C. macropomum. The presence of ostracods and copepods could serve as indicators of parasitic infestations, highlighting the importance of monitoring zooplankton and parasite communities. This approach is valuable for detecting changes in artificial ecosystems, such as fish farms, which could lead to significant long-term effects.